Comparison of single dose versus multiple doses of antibiotic prophylaxis in elective caesarean section - Mishra, Vidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Infectious complications after caesarean delivery (CD) are a substantial cause of maternal morbidity, increase in hospital stay and treatment cost. The spectrum of these complications’ spreads from fever, wound infection, endometritis, urinary tract infection, and some serious complications like pelvic abscess, septic shock and septic pelvic vein thrombophlebitis. To prevent these prophylactic antibiotics have been used however the use of antibiotics should be judicious. Aim was to compare the efficacy of single dose versus multiple doses of antibiotics in elective caesarean section. Methods: This study was conducted in a tertiary care hospital from December 2017 to May 2020. It was a prospective case control study. Sample size was 600, patients were randomly allocated in two groups A and B by card method. Pregnancy category B drug “cefuroxime” was given. Results: Incidence of SSI was 2.7% (n=8) in single dose group and 3% (n=9) in multi-dose group, this difference was not statistically significant. Incidence of fever for more than 48 hours was 1.3% (n=4) in the single dose group and 0.6% (n=2) in multi-dose group, this difference was not statistically significant. Urine R/M for all patients on 3rd post-operative day, in single dose group 2.3% (n=7) patients and in multi-dose group 2.0 % (n=6) patients had more than 5 pus cells. Patients, who had more than 5 pus cells in urine R/M, were subjected to urine culture and sensitivity. Four (1.40%) patients in single dose group had positive cultures (E. coli was detected in three patients and Klebsiella pneumoniae in one) and three (1.0%) patients, in multi dose group, (all the three patients had E. coli in growth). These results were statistically not significant. Conclusions: Single dose antibiotic prophylaxis was found to be comparable to multi-dose antibiotics in our study. Hence it is advocated that single dose antibiotic can be given in elective caesarean section as it is cost effective and as efficient as multi-dose regimen, ensures complete compliance and minimizes side effects and cut-down nursing work-load.